1999
DOI: 10.1097/00005768-199910000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for restricted muscle blood flow during speed skating

Abstract: Consistent with the hypothesis were reductions during skating in VO2peak (4.28 vs 3.83 vs 4.26 L x min(-1)), the VO2 at 4 mmol x L(-1) blood lactate (3.38 vs 1.93 vs 3.31 L x min(-1)), and cardiac output during maximal exercise (33.2 vs 25.3 vs 25.6 L x min(-1)). The reduction in maximal cardiac output was not attributable to differences in HRmax (197 vs 192 vs 193 b x min(-1)) but to a reduction in SVmax (172 vs 135 vs 134 mL x beat(-1)). The reduction in SV appeared to be related to an increased calculated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
95
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(102 citation statements)
references
References 9 publications
7
95
0
Order By: Relevance
“…Firstly, the maximum amount of deoxygenation of the vastus lateralis muscle induced by arterial occlusion was not determined for each subject. Recent studies 31,36 have used a resting cu ischemia protocol (6 ± 8 min of cu ischemia using a blood pressure cu in¯ated to 250 mmHg) to establish maximum tissue deoxygenation levels and have expressed the degree of deoxygenation during exercise relative to this level. This was not done in this study in light of the ®ndings of Chance et al, 11 who reported that the application of cu ischemia to the vastus lateralis muscle following maximal exercise increased the maximum deoxygenation level by only 3%.…”
Section: Muscle Oxygenation Trendsmentioning
confidence: 99%
“…Firstly, the maximum amount of deoxygenation of the vastus lateralis muscle induced by arterial occlusion was not determined for each subject. Recent studies 31,36 have used a resting cu ischemia protocol (6 ± 8 min of cu ischemia using a blood pressure cu in¯ated to 250 mmHg) to establish maximum tissue deoxygenation levels and have expressed the degree of deoxygenation during exercise relative to this level. This was not done in this study in light of the ®ndings of Chance et al, 11 who reported that the application of cu ischemia to the vastus lateralis muscle following maximal exercise increased the maximum deoxygenation level by only 3%.…”
Section: Muscle Oxygenation Trendsmentioning
confidence: 99%
“…Furthermore, the potential of polyphenols to improve blood flow must not be overlooked as restricted blood flow is considered a key limiting factor in muscle oxygenation during high intensity efforts [9]. For instance, it has been shown that restricted blood flow is an important determinant of performance in speed skaters [10]. However, information remains scarce regarding the impact of nutritional products on performance via their impact on vascular function, endothelial function and blood flow [11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research using NIR techniques has centered on laboratory testing using treadmill skating, and has shown that the low sitting position of the skater elicits a lower submaximal VO 2 [7], increased blood lactate concentration [8], and increased quadriceps deoxygenation [4] when compared to upright skating. On-ice tests have shown that skating at higher speeds produces a greater deoxygenation in the quadriceps muscle [8]. The current study utilized a wearable, wireless NIR spectrometer to measure the local muscle oxygenation and blood volume changes during an on-ice race simulation, enabling investigation of the asymmetric effects on right and left legs of skating around a short-track oval.…”
Section: Introductionmentioning
confidence: 99%